Stress Among Older Adults With an Incarcerated Family Member: Testing the Buffering Model of Social Support. (9th August 2021) - Fahmy, Chantal; Testa, Alexander
Abstract: Objectives: This study investigates whether levels of social support moderate the association between age and stress among a sample of individuals who have a family member incarcerated. Methods: Survey responses from individuals who are members of a nonprofit organization for individuals with a family member incarcerated in Texas were used ( n = 376). Ordinary least squares regression analysis was conducted to assess the interaction between age and levels of social support on stress. Results: Findings demonstrated a negative interaction between social support and age ( b = −0.040, p = .027), indicating that higher levels of social support buffer against stress for older adults. Discussion: The theoretical mechanisms linking social support to reductions in stress among older individuals experiencing highly stressful life events (i.e., familial incarceration), as well as the policy and practical implications for enhancing social support among older individuals with a family member incarcerated, are discussed.